William Beall Carrell, MD (1883–1944). Issue 6 (2nd November 2021) - Rizkalla, James M.; Holderread, Brendan; Carpenter, Connor; Nimmons, Scott J. B.; Wilson, Philip; Ellis, Henry
Abstract: This article commemorates Dr. William Beall Carrell, who made many contributions to the field of orthopedic surgery. His legacy continues through the Carrell Clinic and Scottish Rite for Children in Dallas.